﻿Paving the way for a public health renaissance - ﻿Razali Ismail, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2000)
﻿Public Health has been defined as “the provision of health care to groups of populations using public health strategies focusing on preventive aspects of health”. Hence, a Public Health Renaissance would mean a revival of sorts in the field of health care provision to the public from the Public Health viewpoint. In the first place, is there really a need for a Public Health Renaissance? Have the public and/or powers-that-be been so disillusioned with the present state of affairs as to warrant a revival of the whole domain of Public Health? Or is it just a term coined up by a few "visionaries" for something that has been and is already taking place within the domain realm? Are we not already in the midst of this so-called "Renaissance"? And if we are, where are we, how far have we gone and in what form is the "Renaissance" taking place? Come to think of it, what does the process of undergoing a "Renaissance" really entail? Does it essentially involve paradigm shifts and mindset changes of individuals or is it a total revolutionary migration of visions and missions of whole vast organisations and systems? Is it a slow, evolutionary process, allowed to gradually unfold or is it a drastic all-or-nothing event? And does it refer to the "New Public Health" that we have been talking about in recent times?